Diversity and community structure of fish, plankton and benthos in Karangsong Mangrove Conservation Areas, Indramayu, West Java, Indonesia (Biodiversitas Journal of Biological Diversity, 2017)
Sihombing VS, Gunawan H, Sawitri R.2017. Diversity and community structure of fish, plankton and benthos in Karangsong Mangrove Conservation Areas, Indramayu, West Java, Indonesia. Biodiversitas 18: 601-608. The Karangsong Mangrove Conservation Area in Indramayu District, West Java, Indonesia, extending across 20 hectares of coastal land, has undergone eight years of managed revegetation. It has a variety of productive habitats that support the availability of fish resources. The research described in this paper was conducted in July 2016 with the purpose of assessing the diversity, evenness, and structure of fish, plankton and benthos communities as an indicator of the effectiveness of the rehabilitation of the mangrove ecosystem. The fish, benthos, and plankton were collected and analyzed in the Biotrop Laboratories. Fish sampling was carried out using a gill net with mesh size of 25 mm, and with traps. Juvenile fish were collected using a fish net with mesh size of 15 mm, by combing the water column horizontally for 10-15 minutes in the morning and afternoon. For plankton sampling a net No. 25 was used, while samples of benthos were collected using an Ekman Grab sampler. To calculate the community structure and diversity of fish, the study used ecological indices (abundance, dominance, constancy and ecological significance) and diversity indices (Shannon and Simpson diversity). A total of 413 individuals were obtained from 18 fish species, representing 16 families. Family Lutjanidae and Acanthuridae had the highest representative number of species and Pomacentridae showed the highest relative abundance of individuals. The value for the fish diversity index was 2.44 and for the species evenness index was 0.84. The fish population consisted of 44.44% omnivores, 38.89% carnivores and 16.67% herbivores/ detritivores. The highest density of plankton was accounted for by Bacillariophyceae (78.57%), followed by Chlorophyceae (14.29%) and Zooplankton (7.14%). The diversity index for the plankton (H) ranged between 1.040 and 1.462 across habitats, while the evenness index (E) ranged between 0.144 and 1.22. The benthos consisted of Gastropods (83.58%), Crustacea (3.28%), Palaemonidae (1.64%) and Oligochaeta (11.48%). The diversity index for the benthos ranged from 0. 939 to 1. 199 and the evenness index from 0.158 to 0.207. Hence, it may infer from the domination of the environment by Bacillariophyceae and Gastropods, and the low values for diversity index and evenness index, that the area is not particularly good as a fish nursery and breeding habitat. Nevertheless, there are two species of fish that exhibit potential productivity in every habitat; they are Chanos chanos and Scatophagus argus.
Keywords: diversity; fish; plankton; benthos; mangrove